CLINICAL AND RADIOGRAPHIC STUDY REGARDING THE PERI IMPLANT STATUS OF IMPLANTO-PROTETIC REACTIVATED PATIENTS - Bartok Francisc-Florin; Forna Norina-Consuela (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study. The study aimed to determine the prevalence and the evolution stage of the peri-implantitis to patients with implant-prosthetic rehabilitations in relation to demographic and individual factors. Materials and methods. The study group included 51 patients (210 dental implants) with implant-prosthetic restorations (loading age 12-48 months). The clinical exam and radiographic exam were used to assess the periodontal and peri-implant status. Where in doubt regarding the evolution stage of the peri-implantitis, CT exam was performed. Results. The prevalence of peri-implantitis was 83%, with 10% incipient peri-implantitis, 5,7% moderate peri-implantitis and 1,4% severe peri-implantitis Conclusion. The prevalence of peri-implantitis has a high level for patients that avoid regular check-ups and professional cleaning. Some factors (moderate periodontitis, smoker status, age group 40-49) sustain the increase of the peri-implantitis prevalence.